Paradoxes of non-ST-segment elevation acute coronary in real-life clinical practice settings - A. K. Nesova; V. V. Ryabov (Российский кардиологический журнал)
The aim of the review was to identify current barriers, "paradoxes", in the treatment of patients with non-ST segment elevation acute coronary syndrome (NSTE-ACS), based on a critical analysis of modern studies and identified evidence gaps.NSTE-ACS can be considered from the perspective of the following paradoxes: the risk-treatment paradox; risk stratification paradox; scope and timing of dual antiplatelet therapy; paradox of insufficient benefit of invasive treatment; age and comorbidity; tactics for multi-vessel coronary artery disease.A review of publications indexed in the Pubmed and Russian Science Citation Index (RSCI) databases was carried out. The search depth was 10 years (from 2013 to 2023). The search resulted in 328 studies, of which 45 were used to write the final review.